HUBUNGAN JUMLAH EOSINOFIL DENGAN INFEKSI LARVA CACING TAMBANG PADA PENAMBANG PASIR DI DS. BRENGGOLO KECAMATAN KALITIDU BOJONEGORO. - kahar, hartono (Universitas Muhammadiyah Surabaya)
HUBUNGAN JUMLAH EOSINOFIL DENGAN INFEKSI LARVA CACING TAMBANG PADA PENAMBANG PASIR DI DS. BRENGGOLO KECAMATAN KALITIDU BOJONEGORO. Dr.dr. Hartono Kahar, Sp.PK., MQIH. Prodi D3 Analis Kesehatan UM Surabaya Abstract Eosinophils are white blood cells that play a role of granulocytes in the category of the immune system to fight infections and some multicellular parasites on vertebrate creatures. Eosinophils also control the allergic mechanism in the bone marrow, eosinophils will enter the bloodstream and stay in the blood only a few hours, then go into the tissues throughout the body. If a foreign substance enters the body, it would be detected by lymphocytes and neutrophils, which will release the material to attract eosinophils into this area. Eosinophils that occurs in miners exposed to infectious worm larvae will release toxic substances that can kill parasites or worms mines and destroy abnormal cells.The purpose of this study is to determine the relationship of the number of eosinophils with hookworm larvae infection in sand miners in the village. Brenggolo District Kalitidu Bojonegoro. This research uses analytic correlational design using cross sectional (relationships and associations). The number of samples is 49 miners in Ds. Brenggolo Kalitidu Bojonegoro District. By using a random sampling technique ie by random sampling without regard to strata that exist in members of the population.The survey results revealed most of the sand miners eosinophils increased by (44.9%) miners and miners sand worm larvae as much positive (55.1%) miners. Chi Square test calculation results with SPSS statistical test obtained obtained hasi p = 0, the count X2 = 0.000 <a = 0.05, which means that H0 is rejected. Thus it can be said there is a relationship eosinophil count against worm larvae on the sand miners in the Village District Brenggolo Kalitidu Bojonegoro. Keyword : Eosinophils, hookworm larvae infection